(untitled) (The Chittagong University Journal of Science, 2022)
Arsenic (As) is a toxic metalloid widely distributed in the environment posing a serious threat to human health. Enriching the soil with phosphate (Pi) in As condition is believed to reduce the uptake of As in plants. But, it is not clear whether this uptake changes affect the growth behaviors of plant or not. This study, therefore, aimed to determine the efficacy of Pi in balancing the negative effects of As on Cucumis melo as measured in terms of seed germination, seedling growth and biomass production of seedling. The experiment was carried out in petri dish under laboratory conditions in As solution cultures in the absence or presence of Pi. Seeds of C. melo were treated with different concentrations (2, 5 and 10ppm) of As, with or without addition of Pi (10ppm). The results revealed that As exposure hindered germination rate, seedling growth and biomass production of seedling to different magnitudes depending on the concentrations. However, addition of Pi in As solution culture improved the seed germination and seedling growth significantly. Germination were 87% in T1 (2ppm As), 76% in T3 (5ppm As) and 72% in T5 (10ppm As), compared to 90% in T2 (2ppm As+10ppm Pi), 82% in T4 (5ppm As+10ppm Pi) and 77% in T6 (10ppm As+10ppm Pi). In treatments T1 (2ppm As), T3 (5ppm As) and T5 (10ppm As), seedling dry biomasses were 19.8mg, 10.3mg and 7.7mg respectively, which were enhanced to 22.1mg, 15.9mg and 12.1mg respectively in T2 (2ppm As+10ppm Pi), T4 (5ppm As+10ppm Pi) and T6 (10ppm As+10ppm Pi). Similar trend was also recorded for plumule growth, seedling fresh biomass production, seedling vigor, sturdiness etc. Based on the findings, this study recommended the application of Pi to reduce the negative effects of As on C. melo in As solution culture under laboratory condition, that might also be applicable in the field. The Chittagong Univ. J. Sci. 43(1): 51-66, 2021